The Environmental Protection Areas tragedy: an analysis of the implementation of Nature Conservation Units, Brazil - Jeronymo, Carlos André Luz; Silva, Elmo Rodrigues da; Fonseca, Kenny Tanizaki (Ciência e Natura, 2021)
The Environmental Protection Area (EPA) is a management category of the Nature Conservation Unit (UC) of the National System of Nature Conservation Units (NSNCU), Brazil. In 2019, it was the third number of management category sites (n. 355) and the largest in extension in the country, with approximately 50% of the protected coverage of NSNCU. However, there are reports on EPA problems, especially concerning setting and operating their sites. In this paper, we ask, Did the public authorities implant APAs appropriately administrative spheres (federal, state, and municipal) of the public authorities? The hypothesis is that most EPA i) are not implanted. In other words, they are not suitable, enough and ongoing resources, and ii) in completed operation. This article aims to analyze the site’s accomplishment of the EPA management category. The methodological procedures involve a literature review, documentary research, and exploratory research from the National Register of Conservation Units (NRCU) and EPA data. In conclusion, none of EPA complies is following NSNCU, and all of them also need to be implanted and managed in degree.